Benefits of Last Planner® System in mitigation of delay causes in road infrastructure projects - Sánchez, Omar Giovanny; Castañeda, Karen Milady; Herrera, Rodrigo Fernando; Pellicer, Eugenio (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Delay is a phenomenon that affects road infrastructure projects around the world with serious consequences. The study of methodologies that allow mitigate delay causes is a key issue. One option is Last Planner® System (LPS) that is a collaborative planning method that improves the fulfillment of construction activities in time. LPS has the characteristics for mitigate delay causes in early stages and avoid delays happening during the projects. This study analyzes delay causes mitigation through LPS implementation in road infrastructure projects. The research method consisted in: literature review of the main delay causes in road infrastructure projects, benefits identification of LPS implementation in 10 road projects and analysis of relations between delay causes and LPS benefits. The results indicate that many delay causes in road infrastructure projects have relation with: financial difficulties by owner, shortage of materials, inadequate contractor experience. On the other side, the implementation of LPS provides benefits in: time reduction, improvement in communication, early identification of problems and others. Relations between delay causes and benefits show that LPS is an efficient tool for mitigate delay causes in road infrastructure projects.